Autonomy in universities comes with accountability - Abd Razak, Dzulkifli (2008)
THE need for autonomy in institutions of higher learning has been the subject of controversy for a long time in many parts of the world. In Malaysia, it was more so after the 1974 student demonstrations. Underlying it was the issue of mistrust that resulted from such activities. This was followed by the amendments to the Universities and University Colleges Act (Auku), meant to "curb" and act as a deterrent for a wide range of student activities.